(untitled) (Academia Science Repository, 2023)
This article studies how denotative and connotative meanings of words are used in English. Connotation and denotation are a part of language and communication. They are two principal methods of describing the meanings of words. The connotation of a word or term adds elements of emotion, attitude, or colour. The meaning or use of denotation and connotation depends partly on the field of study. It also discusses the types of meanings and groups of denotation and connotation in linguistics.